Machine Learning Methods for Histopathological Image Analysis - Komura, Daisuke; Ishikawa, Shumpei (Computational and structural biotechnology journal, 2018)
Abundant accumulation of digital histopathological images has led to the increased demand for their analysis, such as computer-aided diagnosis using machine learning techniques. However, digital pathological images and related tasks have some issues to be considered. In this mini-review, we introduce the application of digital pathological image analysis using machine learning algorithms, address some problems specific to such analysis, and propose possible solutions.